If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(m + 5) = 40 Reorder the terms: 2x(5 + m) = 40 (5 * 2x + m * 2x) = 40 Reorder the terms: (2mx + 10x) = 40 (2mx + 10x) = 40 Solving 2mx + 10x = 40 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-10x' to each side of the equation. 2mx + 10x + -10x = 40 + -10x Combine like terms: 10x + -10x = 0 2mx + 0 = 40 + -10x 2mx = 40 + -10x Divide each side by '2x'. m = 20x-1 + -5 Simplifying m = 20x-1 + -5 Reorder the terms: m = -5 + 20x-1
| .05x+1.5-.10x=1.15 | | 0.8x(4x-3)+0.3(7-10x)=-0.2 | | 4x-3y=-32 | | 3(x+10)-3=81-3x | | f(x)=((4))/((3x^2-5x^4)^4) | | 9x-4=158 | | [7x+4]+9=4 | | 0.5x-0.4x(3x+8)=0.3 | | (4)/((3x^2)-(5x^4))^4 | | 3y+2(y-4)=2 | | (11((x-7)/2)^2)-20=101 | | 15/9=8/5 | | (4)/((3x^2-5x^4)^4) | | 3x+13=90 | | ((4)/((3x^2-5x^4)^4)) | | f(x)=(4)/(3x^2-5x^4)^4 | | 9x-4=39.5 | | (4)/(3x^2-5x^4)^4 | | -10-m=-70 | | 36=(90/360)*x*x | | 4a-14=2a | | (4/5)-(2x/3)=(3/10) | | (x-3)(x+1)=x*-11 | | n^3-64/125 | | 3m-1-36=11 | | 3.16x+x= | | (X-3)(x+1)=x*11 | | 5n-7=32 | | m-39+93-13=36 | | log(22/x) | | x-.1=18000 | | 9x^2+18x-45=5 |